The Effectiveness of Using the SQ3R Method in Improving Maharah Qira'ah in Balaghah Learning at Al-Muhibbin Islamic Boarding School Tambakberas Jombang (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2022)
This research comes from the results of observations of researchers at the Al-Muhibbin Islamic Boarding School Tambakberas Jombang, where in Balaghah learning, the ability to read material is meager, so it affects the level of understanding of students on Balaghah reading material besides the value of students in Balaghah learning is also common. So departing from this, the researchers used the SQ3R method, which was applied to the Al-Muhibbin students in learning Balaghah. This study aims to 1) determine the level of understanding of maharah qira'ah before and after the application of the SQ3R method in learning Balaghah at the Al-Muhibbin Islamic Boarding School Tambakberas Jombang; 2) to determine the effectiveness of using the SQ3R method in increasing maharah qira'ah in Balaghah learning at Al-Muhibbin Islamic Boarding School Tambakberas Jombang. The type of this research is quantitative research with the One-Group Pretest-Postest Design Research. The population of this study was all students of Al-Muhibbin Tambakberas Jombang, with a total of 1300 students. The sample in this study was 40 students. The research instrument used a test of understanding maharah qiraah, documentation, and observation sheets and then analyzed by descriptive and inferential analysis. The results of this study are 1) after the SQ3R method treatment showed that the understanding of the maharah qira'ah of students in Balaghah learning at the Al-Muhibbin Islamic Boarding School Tambakberas Jombang increased, they could conclude that the contents of the reading and understand the Balaghah material contained in the reading; 2) the effectiveness of the SQ3R method in learning Balaghah understanding of the maharah qira'ah of students in Balaghah learning at the Al-Muhibbin Islamic Boarding School Tambakberas Jombang can be concluded to experience a significant increase, as evidenced by the pre-test scores of students, namely 65 and post-test students of 78. So, it can be concluded that the use of the SQ3R method has high effectiveness in understanding the maharah qira'ah of students in Balaghah learning at the Al-Muhibbin Islamic Boarding School Tambakberas Jombang.
Keywords: SQ3R Method, Maharah Qira’ah, Balaghah.